2014
DOI: 10.1159/000369170
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Green Tea Catechins with Breast Cancer Endocrine Treatment: A Systematic Review

Abstract: Recent data have shown strong chemopreventive and possibly cancer chemotherapeutic effects of green tea polyphenols and EGCG against breast cancer. This systematic review aims to synthesize data on the possible interaction of green tea catechins with breast cancer endocrine treatment. Electronic databases were searched with the appropriate search terms. Experimental trials suggest a synergistic interaction of green tea catechins with tamoxifen or raloxifene in the treatment of estrogen receptor-positive and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Several authors have addressed the hypothesis of adding green tea to breast cancer therapy (34,35). In particular, the coadministration of green tea and tamoxifen seems to improve the outcomes in breast cancer cell lines (36,37) and animal models (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have addressed the hypothesis of adding green tea to breast cancer therapy (34,35). In particular, the coadministration of green tea and tamoxifen seems to improve the outcomes in breast cancer cell lines (36,37) and animal models (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from several laboratory studies has demonstrated the strong chemopreventive and potentially cancer chemotherapeutic effects of the major green tea constituent, epigallocatechin-3-gallate (EGCG), against breast cancer (70). Most experimental data have shown that green polyphenols can modulate multiple signalling pathways and regulate the growth, survival and metastasis of cancer cell at multiple levels (71,72).…”
Section: Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%
“…EGCG also targets molecules that regulate cell motility, invasion and metastasis, such as the HER family, vascular endothelial growth factor receptor (VEGFR), matrix metalloproteinases (MMPs), 67-kDa laminin receptor (67LR) and the phosphatidylinositol-3-kinase (PI3K)-Akt pathway [812]. Furthermore, EGCG is an interesting molecule for adjuvant combined therapies, as it can improve the efficacy of chemotherapeutics currently used in cancer therapy (tamoxifen, doxorubicin and cisplatinum) by promoting synergistic cytotoxic effects [1316]. The strategy of combining EGCG with chemotherapeutics might become a potential vehicle to reduce drug-related toxicities in patients treated for cancer.…”
Section: Introductionmentioning
confidence: 99%